An Inclusive Approach to Teaching Quantum Mechanics in Secondary School - Leonardo Colletti (MDPI AG, 2023)
Quantum physics is not only a fundamental part of physics education per se but could offer an opportunity to develop cultural tools also relevant outside the boundaries of physics, for instance helping raise awareness about basic cognitive patterns or providing a model for how science works and grows. Given this kind of significance, when it comes to teaching quantum mechanics in secondary school, instructors should be as inclusive as possible; rather than working out its mathematical or technical aspects, which ultimately may turn out inadequate at this level, they should try to make sense of the subject, so that students not oriented toward a STEM-related career are also given the possibility of appreciating the cultural depths reached by physics. Therefore, based on my experience with numerous classes and by making broad reference to the philosophical discipline of hermeneutics, I argue that quantum mechanics represents an invaluable opportunity for each and every learner to broaden and enrich his or her set of cognitive tools with which to make sense of both the outer and inner world. An essential but decade-long qualitative survey clearly shows that by approaching quantum physics with this purpose, all physics and science itself acquire a new relevance in students' and society's eyes.